2004
DOI: 10.1007/s00204-003-0536-x
|View full text |Cite
|
Sign up to set email alerts
|

Low glutathione S -transferase dogs

Abstract: Liver and kidney glutathione S-transferase (GST) activities to 1,2-dichloro-4-nitrobenzene (DCNB) as a substrate (GST-D activities) were measured in 280 dogs from five different breeders, and significant individual differences in this activity were observed in both organs. Interestingly, 34 out of the 280 dogs (i.e. 12.1%) were those in which liver GST-D activities were less than 10 nmol/min per mg cytosolic protein, "low GST dogs", and the other dogs were classified as "middle" and "high" GST dogs for which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 39 publications
3
19
0
1
Order By: Relevance
“…In particular, the dog appears to be one of the domestic species most sensitive to the effects deriving from intoxication by aflatoxins, most likely because of the low activity of glutathione S-transferase, which is involved in the detoxification of these mycotoxins (Watanabe et al, 2004). In acute forms of aflatoxicosis, dogs exposed to doses exceeding 500-1000 g/kg of BW died within a few days, showing signs of hepatic hyperplasia, disseminated intravascular coagulation and hemorrhages.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the dog appears to be one of the domestic species most sensitive to the effects deriving from intoxication by aflatoxins, most likely because of the low activity of glutathione S-transferase, which is involved in the detoxification of these mycotoxins (Watanabe et al, 2004). In acute forms of aflatoxicosis, dogs exposed to doses exceeding 500-1000 g/kg of BW died within a few days, showing signs of hepatic hyperplasia, disseminated intravascular coagulation and hemorrhages.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have found significant associations between canine lymphoma and exposure to industrial pollutants, solvents and herbicides, but the role of specific environmental carcinogens in the development of lymphoma in dogs is not clear . GSTT1 activities have been characterized in livers from research beagles, and 12% of these dogs had virtually no GSTT1 protein expression or activity . However, the genetic basis for this variability, and its toxicological consequences, has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…9 Dogs appear more susceptible because of their inherently lower hepatocellular concentration of GSH compared with other species, as well as their inter-individual differences in activity of GSH-S-transferase. 13,14 Furthermore, AF are reported to exert an anti-coagulation effect as a result of their coumarin-like structure. 15 Exposure to lower AF concentrations in feed over a prolonged period can induce chronic liver failure, indicating a cumulative effect.…”
mentioning
confidence: 99%